Craniopharyngiomas : comprehensive diagnosis, treatment and outcome - Kenning, Tyler J.; Evans, James J.; ScienceDirect eBooks (Oxford : Academic Press, 2015)
Craniopharyngiomas: A Comprehensive Guide to Diagnosis, Treatment and Outcome is a comprehensive guide to the science, diagnosis and treatment of craniopharyngiomas, rare brain tumors that grow near the pituitary gland. Even though these tumors are generally benign, due to the location, prognosis was often bleak. This reference provides a resource for specialists requiring a comprehensive overview of this rare form of tumor, outlining new diagnostic, imaging and surgical techniques, including endoscopic endonasal cranial base surgery, which enable successful neurosurgical intervention. With a.
Print version record.
Includes bibliographical references and index.
Elsevier
Keywords: Intracranial tumors; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Intracranial tumors; Craniopharyngioma -- diagnosis; Electronic books